2022
DOI: 10.1088/1361-648x/ac4fe8
|View full text |Cite
|
Sign up to set email alerts
|

The generalized continuous multiple step (GCMS) potential: model systems and benchmarks

Abstract: The Generalized Continuous Multiple Step (GCMS) potential is presented in this work. Due to its flexibility, repulsive and/or attractive contributions are encodable through adjustable energy and length scales. The GCMS interaction provides a continuous representation of square-well, square-shoulder potentials and their variants for implementation in computer simulations. A continuous and differentiable energy representation is required to derive forces in conventional simulation algorithms. Molecular Dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 156 publications
1
4
0
Order By: Relevance
“…In the present paper we have also shown that the compressibility factor of such systems derived with the RFA, using either the virial or the compressibility routes, is also reasonably accurate. Finally, the good agreement between our results for the RDF and the simulation data (obtained with an equivalent continuous potential) [11] suggests that, at least for the structural and thermodynamic properties, replacing discrete potentials with (appropriate) continuous ones [24] does not lead to serious errors.…”
Section: Discussionsupporting
confidence: 67%
“…In the present paper we have also shown that the compressibility factor of such systems derived with the RFA, using either the virial or the compressibility routes, is also reasonably accurate. Finally, the good agreement between our results for the RDF and the simulation data (obtained with an equivalent continuous potential) [11] suggests that, at least for the structural and thermodynamic properties, replacing discrete potentials with (appropriate) continuous ones [24] does not lead to serious errors.…”
Section: Discussionsupporting
confidence: 67%
“…46 In this work, the pHD was accomplished by using the continuous generalized continuous multiple step (GCMS) potential, which incorporates an excluded volume contribution. 47 The GCMS potential has the following formwhere q is related to the potential force and ω (positive definite) defines the spatial extent of the particle nucleus in units of σ . For hard discs, the parameter ω is arbitrary and a 0 = 0.…”
Section: Simulation Models and Methodologymentioning
confidence: 99%
“…46 In this work, the pHD was accomplished by using the continuous generalized continuous multiple step (GCMS) potential, which incorporates an excluded volume contribution. 47 The GCMS potential has the following form…”
Section: Interaction Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid this problem there have been some works reported in the literature that provide a continuous version of some discontinuous potentials that are able to accurately describe the properties of the equivalent original discontinuous potential. With this goal in mind, the second contribution by Munguía-Valadez et al [14] presents a generalized continuous multiple step interaction potential that provides a continuous representation of the square-well, square-shoulder potentials and for some combinations of them for their implementation in simulations.…”
Section: Interaction Potentials In Soft Mattermentioning
confidence: 99%